Cell Transplantation Combined with Recombinant Collagen Peptides for the Treatment of Fabry Disease. (8th December 2020) - Kami, Daisuke; Yamanami, Masashi; Tsukimura, Takahiro; Maeda, Hideki; Togawa, Tadayasu; Sakuraba, Hitoshi; Gojo, Satoshi
Fabry disease is caused by a decrease in or loss of the activity of alpha-galactosidase, which causes its substrates globotriaosylceramide (Gb3) and globotriaosylsphingosine (lyso-Gb3) to accumulate in cells throughout the body. This accumulation results in progressive kidney injury due to glomerulosclerosis and in heart failure due to hypertrophy. Enzyme replacement therapy (ERT) has been used as the standard therapy for Fabry disease, but it causes a significant financial burden, and regular administration is inconvenient for patients. Because of the short half-life of alpha-galactosidase in vivo, therapeutic methods that can supplement or replace ERT are expected to involve continuous release of alpha-galactosidase, even at low doses. Cell transplantation therapy is one of these methods; however, its use has been hindered by the short-term survival of transplanted cells. CellSaic technology, which utilizes cell spheroids that form after cells are seeded simultaneously with a recombinant collagen peptide scaffold called a μ-piece, has been used to improve cell survival upon implantation. In this study, syngeneic murine embryonic fibroblasts were used to generate CellSaic that were transplanted into Fabry mice. These spheroids survived for 28 days in the renal subcapsular space with forming blood vessels. These results indicate CellSaic technology could be a platform to promote cellular graft survival and may facilitate the development of cell transplantation methods for lysosomal diseases.